THE EFFECT OF USING REAP (READ, ENCODE, ANNOTATE, PONDER) STRATEGY ON READING COMPREHENSION OF NARRATIVE TEXT OF THE FIRST YEAR STUDENTS OF SMAN 1 TEBING TINGGI TIMUR MERANTI - ', Novilismanita; Prawati, Atni; ', Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was designed to investigate whether there is a significant effect of using Read Encode Annotate Ponder strategy on reading comprehension of narrative text of the first year students of SMAN 1 Tebing Tinggi Timur Meranti. This research took place at SMAN 1 Tebing Tinggi Timur Meranti from April to june 2017. The sample was 40 students from X.2 Social that took by using cluster sampling technique. The test containing 40 items was used to collect the data. The technique of data analysis was paired sample t-test. The research findings found that there was a significant difference of students’ reading comprehension on narrative text after being taught through Read Encode Annotate Ponder strategy. Based on the data analysis, it was found that t-test (7.051)was bigger than t-table (2.023). This suggested that REAP strategy was effective in teaching reading narrative text.Keywords: Read Encode Annotate Ponder, Reading Comprehension, Narrative Text